2011
DOI: 10.4025/actasciagron.v33i1.5062
|View full text |Cite
|
Sign up to set email alerts
|

Modelos agro-meteorológicos na estimativa da produtividade da cultura da soja na região de Ponta Grossa, Estado do Paraná

Abstract: RESUMO. O presente estudo teve por objetivo avaliar o desempenho de modelos simplificados e agro-meteorológicos na estimativa da produtividade da cultura da soja, na região de Ponta Grossa, Estado do Paraná, visando à previsão e ao planejamento de safras. A região estudada possui Latossolo Vermelho distrófico típico e clima Cfb. Os dados de produtividade da cultura da soja (11 safras) e climáticos foram disponibilizados pela Fundação ABC e Simepar, respectivamente. A evapotranspiração de referência foi estimad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
4
1
1
Order By: Relevance
“…Therefore, both methods can be used equally to estimate soybean yield (Table 2). These results are slightly lower than those obtained by Araújo et al (2011), who found an estimated yield of 3567 kg ha −1 , but for only one region and growing season in the state of Paraná. The average estimated yield was 12% higher than the average yield officially reported in Brazil and 6% higher than the average observed in the state (CONAB, 2018).…”
Section: Yield Estimationscontrasting
confidence: 77%
See 2 more Smart Citations
“…Therefore, both methods can be used equally to estimate soybean yield (Table 2). These results are slightly lower than those obtained by Araújo et al (2011), who found an estimated yield of 3567 kg ha −1 , but for only one region and growing season in the state of Paraná. The average estimated yield was 12% higher than the average yield officially reported in Brazil and 6% higher than the average observed in the state (CONAB, 2018).…”
Section: Yield Estimationscontrasting
confidence: 77%
“…An HI value of 0.26 was used as a calibration index in this study. Moreover, the indices obtained in the literature do not allow obtaining statistically satisfactory yield estimates with the agrometeorological models (Araújo et al, 2011). Steduto et al (2012) recommended that HI values should be calibrated for each region.…”
Section: Yield Estimationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A partir da identificação dos modelos agrometeorológicos que melhor descrevem o comportamento da cultura da soja em uma determinada região, é possível utilizar algoritmos para a simulação da produtividade (Silva-Fuzzo et al, 2015;Klering et al, 2016), ou mesmo inseri-los em sistemas de apoio à decisão (Araujo et al, 2011).…”
Section: Introductionunclassified
“…However, this method uses several parameters not always observed or measured in weather stations, thus encouraging studies to establish more simplified alternative methods for evapotranspiration estimation (Borges Júnior et al, 2012;Pilau et al, 2012;Bezerra et al, 2014;Oliveira et al, 2020). Some mathematical (current agrometeorological) models may act as efficiency indicators, since they consider the action of each meteorological element on crop yield, which can be described (Araujo et al, 2011;Gomes et al, 2014;Sentelhas et al, 2015;Silva et al, 2020). Thus, agrometeorological modeling involves the action of meteorological elements observed on crop traits, aggregating biomass accumulation or loss over time.…”
Section: Introductionmentioning
confidence: 99%